Heuristic Cues for Meta-Reasoning Judgments: Review and Methodology - Rakefet Ackerman (Psychological Topics, 2019)
Metacognitive research aims to explain how people regulate their effort when performing cognitive tasks, to expose conditions that support reliable monitoring of chance for success, and to provide a basis for developing improvement guidelines. The essence of the domain is that monitoring drives control: people continually self-assess their chance for success before, during, and after performing a cognitive task, and use these judgments to guide their effort-allocation decisions (e.g., whether to reconsider an answer option, change strategy, seek help, or give up). Thus, factors that underlie metacognitive judgments affect the efficiency with which people perform cognitive tasks. This paper focuses on meta-reasoning – the monitoring and control processes that apply to reasoning, problem-solving, and decision-making tasks. So far, relatively little is known about heuristic cues used for inferring meta-reasoning judgments. This paper reviews the known heuristic cues and offers methodological guidelines for a critical reading of existing research and for designing high-quality studies that will advance this important domain.